2011
DOI: 10.2118/129675-pa
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Systems for EOR in High-Temperature, High-Salinity Environments

Abstract: Summary A systematic study was made of phase behavior of alkoxyglycidylether sulfonates (AGESs). These surfactants were screened with either NaCl-only brines or NaCl-only brines and n-octane at water/ oil ratio (WOR) ~1 for temperatures between approximately 85 and 120°C. All test cases were free of alcohols and other cosolvents. Classical Winsor phase behavior was observed in most scans, with optimal salinities ranging from less than 1% NaCl to more than 20% NaCl for AGESs with suitable combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 17 publications
2
95
0
Order By: Relevance
“…They are shown in Fig. 4 (Barnes et al, 2008;Goethals et al, 2001;Hirasaki et al, 2004;Puerto et al, 2010;Scorzza et al, 2002a, b).…”
Section: Background Of Hld Variable Correlation Solubilization Intementioning
confidence: 94%
“…They are shown in Fig. 4 (Barnes et al, 2008;Goethals et al, 2001;Hirasaki et al, 2004;Puerto et al, 2010;Scorzza et al, 2002a, b).…”
Section: Background Of Hld Variable Correlation Solubilization Intementioning
confidence: 94%
“…This issue, particularly high-salinity problems, is not discussed here since it has been extensively reported in the literature, with many examples, although without quantitative rules [82,[84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Insensitivity To a Formulation Variable Change Reduced Sensimentioning
confidence: 99%
“…No birefringent phase was found under optical microscopy observation with crossed polarizers for all samples (not shown here). It is noteworthy that Puig et al (1982) showed that vesicles made from the lamellar phase of a single anionic surfactant by sonication could pass through Berea sandstone with low retention. However, vesicles from a single surfactant are thermodynamically unstable and revert to the lamellar phase over time.…”
Section: Salinity (% Nacl)mentioning
confidence: 99%